Analisis Hubungan Sistem Pencahayaan dengan Kelelahan Mata pada Pegawai Perkantoran - Fain Roudlotull Jannah; Moch. Sahri; Friska Ayu; Bondan Winarno (Jurnal Ilmiah Wahana Pendidikan, 2022)
Lighting is one of the potential hazards and included in physical factors. If the quality of lighting in a room is not up to standard, it will be at risk to affect the comfort and safety of space users. This study aims to analyze the relationship between lighting systems and eye fatigue on employees in the ABC Division at the XYZ Office of Gresik Regency. This study is an analytic observational study with a cross-sectional. The sample in this study were 13 respondents using a total sampling technique. Measurement of lighting intensity was done using a lux meter and eye fatigue was measured using a Visual Fatigue Index. To see the strength of the relationship between variables, the Contingency Coefficient. The results showed 11 points (84.6%) with lighting intensity that not up to standards and 11 employees (84.6%) experienced eye fatigue. The lighting system has the strongest relationship with eye fatigue (P Value =0.707). Recommendations that can be given are to check the cleanliness and function of the armatures and lamps regularly, change the color of wall paint regularly, install curtains on windows, fill the room with green ornamental plants, socializing and implementing about 5R culture and eye stretching.